Employing Running Dictation for Developing Students’ Vocabulary Mastery for the Tenth-Grade Students of SMAN 1 Nita - Sesilia Selvina; Marselus Yumelking; Genoveva Dua Eni (Journal of Innovative and Creativity, 2026)
The objectives of the study were to improve the students’ vocabulary mastery in writing skills, to implement the Running Dictation Technique, and to determine the students’ responses toward the use of running dictation. The method of the research employed a Classroom Action Research (CAR) with the subjects of the research were 18 tenth-grade students of Class X-C selected through purposive sampling. Data were collected using vocabulary writing tests, observations, interviews, and field notes. The results indicated that the mean score improved from 62.35 in Cycle I, with 22.22% class percentage, to 77.26 in Cycle II, with 77.78% class percentage, and reached 87.44 in Cycle III, with 100% class percentage. The results of observation showed that the running dictation technique was implemented through the following stages: first, the researchers posted 5 sheets. Then, the teacher divided the students into 5 groups. Next, the teacher gave the students the opportunity to choose the first runner and writer in each group. Before the game started, the researchers explained the rules of the game and informed the students of the duration of the game. When the game began, the runners and writers had enough time to remember and comprehend the text before dictating it to their partners in order to minimize mistakes. The researchers repeatedly reminded each group to understand the texts using the pictures and to write the Indonesian translation after the English sentences. The researchers also reminded the students to rotate roles within the group until the entire text was completed. The results of the winning group were also announced to provide recognition and reward for the students’ efforts. The results of students’ responses were that the students became more enthusiastic in playing; they were also able to translate the texts more quickly and simply before submitting them.